RSV Prevention in All Infants: Which Is the Most Preferable Strategy? - Esposito, Susanna; Abu Raya, Bahaa; Baraldi, Eugenio; Flanagan, Katie; Martinon Torres, Federico; Tsolia, Maria; Zielen, Stefan (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) causes a spectrum of respiratory illnesses in infants and young children that may lead to hospitalizations and a substantial number of outpatient visits, which result in a huge economic and healthcare burden. Most hospitalizations happen in otherwise healthy infants, highlighting the need to protect all infants against RSV. Moreover, there is evidence on the association between early-life RSV respiratory illness and recurrent wheezing/asthma-like symptoms As such, RSV is considered a global health priority. However, despite this, the only prevention strategy currently available is palivizumab, a monoclonal antibody (mAb) indicated in a subset of preterm infants or those with comorbidities, hence leaving the majority of the infant population unprotected against this virus. Therefore, development of prevention strategies against RSV for all infants entering their first RSV season constitutes a large unmet medical need. The aim of this review is to explore different immunization approaches to protect all infants against RSV. Prevention strategies include maternal immunization, immunization of infants with vaccines, immunization of infants with licensed mAbs (palivizumab), and immunization of infants with long-acting mAbs (e.g., nirsevimab, MK-1654). Of these, palivizumab use is restricted to a small population of infants and does not offer a solution for all-infant protection, whereas vaccine development in infants has encountered various challenges, including the immaturity of the infant immune system, highlighting that future pediatric vaccines will most likely be used in older infants (>6 months of age) and children. Consequently, maternal immunization and immunization of infants with long-acting mAbs represent the two feasible strategies for protection of all infants against RSV. Here, we present considerations regarding these two strategies covering key areas which include mechanism of action, “consistency” of protection, RSV variability, duration of protection, flexibility and optimal timing of immunization, benefit for the mother, programmatic implementation, and acceptance of each strategy by key stakeholders. We conclude that, based on current data, immunization of infants with long-acting mAbs might represent the most effective approach for protecting all infants entering their first RSV season.